2023
DOI: 10.1002/for.2977
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting nonperforming loans using machine learning

Abstract: Nonperforming loans play a critical role in financial institutions' overall performance and can be controlled by forecasting the probable nonperforming loans. This paper employs a series of machine learning techniques to forecast bank nonperforming loans on emerging countries' financial institutions. Using quarterly cross‐sectional data of 322 banks from 15 emerging countries, this study finds that advanced machine learning‐based models outperform simple linear techniques in forecasting bank nonperforming loan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 68 publications
(113 reference statements)
0
2
0
Order By: Relevance
“…Their experimental results demonstrated a significant improvement, surpassing the 80% accuracy threshold, offering promising implications for the financial sector. In (Abdullah et al, 2023), the research objective focused on forecasting nonperforming loans in financial institutions, recognizing their significance in overall performance. Employing machine learning techniques, the study utilized quarterly cross-sectional data from 322 banks in 15 emerging countries.…”
Section: Related Workmentioning
confidence: 99%
“…Their experimental results demonstrated a significant improvement, surpassing the 80% accuracy threshold, offering promising implications for the financial sector. In (Abdullah et al, 2023), the research objective focused on forecasting nonperforming loans in financial institutions, recognizing their significance in overall performance. Employing machine learning techniques, the study utilized quarterly cross-sectional data from 322 banks in 15 emerging countries.…”
Section: Related Workmentioning
confidence: 99%
“…Abdullah and colleagues (2023) [10] explored a range of machine learning techniques to forecast nonperforming loans within financial institutions in emerging countries. By examining the data from 322 banks spanning 15 nations, their comprehensive analysis revealed that advanced machine learning models, particularly random forest, surpassed linear methods, achieving an accuracy of 76.10%.…”
Section: Related Researchmentioning
confidence: 99%